2021
DOI: 10.1186/s12940-021-00747-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal bisphenol urine concentrations, fetal growth and adverse birth outcomes: A population-based prospective cohort

Abstract: Background Exposure to bisphenols may affect fetal growth and development. The trimester-specific effects of bisphenols on repeated measures of fetal growth remain unknown. Our objective was to assess the associations of maternal bisphenol urine concentrations with fetal growth measures and birth outcomes and identify potential critical exposure periods. Methods In a population-based prospective cohort study among 1379 pregnant women, we measured m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The epididymal sperm density was decreased. In 2002, Bemard et al fed 2 generations of SD rats with PCP, and reproductive toxicity tests showed that high-dose (60 mg/(kg.d)) feeding caused delayed sexual maturation, reduced sperm number, reduced prostate and testes, reduced embryo implantation capacity, and reduced litter production [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epididymal sperm density was decreased. In 2002, Bemard et al fed 2 generations of SD rats with PCP, and reproductive toxicity tests showed that high-dose (60 mg/(kg.d)) feeding caused delayed sexual maturation, reduced sperm number, reduced prostate and testes, reduced embryo implantation capacity, and reduced litter production [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study are as follows: incorporating observational studies in the study is limited, the follow-up varies from 3 to 36 months, making the evaluation of long-term complications, the publication bias analysis is only qualitative and large personal factors, and the two techniques described in this study contain multiple surgical procedures, which may increase the bias of the article. Since the assessments were all based on a small number of studies [ 26 28 ], the results must be interpreted with caution. As the accumulated evidence grows, our conclusions may either be supported or overturned.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the lowest BPS dose that exerted a significative effect on cell invasion was 100 ng/mL BPS, a dose within the urinary BPS concentration range observed in the U.S. (0.07 to 211.9 ng/mL; [ 10 ]). While in vivo exposure to BPS can result in cell fusion defects in an ovine model [ 23 ], effects of BPS in human pregnancies have been associated with both higher [ 56 ] and lower [ 57 ] birth weight and birth length. Thus, whether BPS can interfere with EGF signaling, in vivo, in humans, resulting in poor pregnancy outcomes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…2019 ; Santos et al. 2021 ; Sol et al. 2021 ) but used different model structures, exposure and outcome parameterizations, and covariate sets based on the research questions of each study.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we created single-pollutant regression models to estimate the individual chemical biomarker associations with fetal growth parameters. These estimates have been previously published (Ferguson et al 2019;Santos et al 2021;Sol et al 2021) but used different model structures, exposure and outcome parameterizations, and covariate sets based on the research questions of each study. Thus, we replicated those analyses here with the same primary model structure (i.e., averaged biomarkers over pregnancy in association with growth measurements at each time point) and with the same covariates included in our primary model for more direct comparison with our results.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%